Advances in software engineering and knowledge engineering (World Scientific, 1993)
The papers collected in this book were invited by the editors as tutorial courses or keynote speeches for the Fourth International Conference on Software Engineering and Knowledge Engineering. The book offers wide coverage of the main topics involved with the specifications, prototyping, development and maintenance of software systems and knowledge-based systems. The main issues in the area of software engineering and knowledge engineering are addressed and for each analyzed topic the corresponding research state is reported.